Hubungan Obesitas dengan Usia, Jenis Kelamin, Genetik, Asupan Makanan dan Kebiasaan di Dusun Bangkan - Eka Risdayani; Armanto Makmun (Yayasan Citra Cendekia Celebes, 2021)
Background: Obesity is a condition of excess fat accumulation in the body's adipose tissue which can be influenced by physical activity, food intake, genetic factors, sleep habits, age and gender. The incidence rate in Indonesia tends to increase as seen from the Riskesdas 2007, 2013 and 2018 data, namely 10.5%, 14.8%, and 21.8%. The aimed of the reaserach is to determine the relationship between obesity and age, gender, level of physical activity, eating habits, genetics and sleep duration. This research is a quantitative study with a cross sectional approach. Data collection was carried out through a questionnaire. The research sample is a sample with overweight and obesity obtained a sample of 80 samples. The data analysis was conducted, namely univariate and bivariate analysis using the chi-square test. The result, 36.3% of respondents are overweight and 63.8% obese. Most of the respondents were> 18 years old. The results showed that obesity was significantly associated with age (p = 0.016), gender (p = 0.010), physical activity (p = 0.025), frequency of eating (p = 0.015), frequency of heavy eating (p = 0.040), drinking- sugary drinks (0.025), fast food (p = 0.025) daily portions of food (p = 0.025) and a family history of obesity (p = 0.007). Conversely, consumption of snacks (p = 0.731), consumption of fibrous foods (p = 0.089), the relationship between breakfast (p = 0.776), the relationship between sleep time (p = 0.243). Age, gender, physical activity, frequency of eating, frequency of heavy eating, drinking sugary drinks, consumption of fast food, daily food portions and a family history of obesity have a significant relationship which can be a contributing factor to obesity.